Railway Ecology 2017
DOI: 10.1007/978-3-319-57496-7_2
|View full text |Cite
|
Sign up to set email alerts
|

Current Knowledge on Wildlife Mortality in Railways

Abstract: Wildlife mortality on roads has received considerable attention in the past years, allowing the collection of abundant data for a wide range of taxonomic groups. On the contrary, studies of wildlife mortality on railway tracks are scarce and have focused primarily on a few large mammals, such as moose and bears. Nevertheless, many species are found as victims of collisions with trains, although certain taxonomic groups, such as amphibians and reptiles, and/or small bodied species are reported infrequently and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 19 publications
0
20
0
1
Order By: Relevance
“…Although it is usually assumed that anthropogenic barriers such as railways have an adverse effect on animal populations (Santos et al 2017), it turns out that some species can benefit from them (Li et al 2010;Morelli et al 2014). For example, several species of birds use railways as attractive foraging areas, sources of gastroliths, or sand-bathing locations where they can clean their feathers (Morelli et al 2014;Lucas et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is usually assumed that anthropogenic barriers such as railways have an adverse effect on animal populations (Santos et al 2017), it turns out that some species can benefit from them (Li et al 2010;Morelli et al 2014). For example, several species of birds use railways as attractive foraging areas, sources of gastroliths, or sand-bathing locations where they can clean their feathers (Morelli et al 2014;Lucas et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Sieler and olsson (2017) reported that the per-kilometer impact of railways on wildlife in Sweden exceeds that of highways, with significant associated economic impact. Santos et al (2017) reported that the Sociedad Conservación Vertebrados had found that 36.5 vertebrates/km/year are killed on Spanish railways. Like highways, all wildlife taxa are subject to mortality from trains (Santos et al 2017, Wildlife Institute of India 2016).…”
Section: Wildlife-vehicle Collisionsmentioning
confidence: 99%
“…Much of the knowledge related to railway impacts on wildlife from collisions has been focused on ungulates (e.g., moose) and bears in northern climes (Waller and Serhveen 2005, Seiler and Helldin 2006, van der Grift 1999, Santos et al 2017, Seiler and olsson 2017. dorsey et al (2015,2017) found that railway collisions with wildlife were tied to several factors including animal abundance, train > Hit-and-run victim.…”
Section: Wildlife-vehicle Collisionsmentioning
confidence: 99%
“…The types of linear structures differ in terms of risks posed to wildlife populations as well as in the understanding of how to mitigate these effects. Research from the fields of road ecology and railway ecology points to two factors that account for most of the negative effects of linear structures on wildlife [5][6][7][8][9][10]. The first factor is direct mortality, which is caused by, for example, wildlife-vehicle collision (wvc) and wildlife-train collision (wtc) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%